Association between neutrophil percentage to albumin ratio and sarcopenia among cancer patients: evidence from both the Chinese and American cohorts - Yu, Yang; Chen, Bo (Frontiers in Nutrition, 2026)
BackgroundSarcopenia, the progressive depletion of skeletal muscle mass and strength, worsens quality of life, and survival in cancer patients. Given its multifactorial pathogenesis involving chronic inflammation and malnutrition, integrated biomarkers for early risk assessment are needed.MethodsThis two-cohort study investigated the clinical utility of the neutrophil percentage-to-albumin ratio (NPAR) for sarcopenia risk stratification. We analyzed data from the US National Health and Nutrition Examination Survey (NHANES, n = 1,586) and a Chinese clinical cohort (n = 705). Associations were assessed using multivariable regression, threshold analysis, and ROC curves. Mediation analyses were performed in the NHANES cohort.ResultsElevated NPAR was significantly associated with higher odds of sarcopenia in both the American (OR = 1.14, 95% CI: 1.06–1.22) and Chinese (OR = 1.10, 95% CI: 1.04–1.14) populations, showing a dose-response relationship. Non-linear threshold effects were identified at NPAR = 14.7 (NHANES) and NPAR = 17.07 (Chinese cohort). NPAR outperformed other inflammatory indices in the clinical cohort (AUC = 0.568). Systemic inflammation (C-reactive protein) and dietary protein intake mediated 17.10% and 6.37% of the association, respectively. Sensitivity analyses supported robustness.ConclusionsNPAR is a practical and cost-effective inflammatory-nutritional biomarker for sarcopenia risk stratification in cancer patients. It shows promise for early identification and personalized intervention across diverse populations.